The Effect of Hatch and Carry Distance of Elaeidobius Kamerunicus on Fruit Set and Bunch Weight of Oil Palm (Elaeis guineensis Jacq.) - Hartono, Hartono; Susanto, Agus; Kurniawan, Indra; Saloko, Subakho Aryo; Putra, Arief Panca; Nurcahyono, Nurcahyono (Tropical Plantation Journal, 2026)
Hatch and carry is a breeding and distribution system for the primary pollinator of the oil palm, Elaeidobius kamerunicus. Information on the optimal distance for the Hatch and Carry application on pollination success and bunch productivity is still limited. This study aims to determine the effective distance of Hatch and Carry on fruit set and bunch weight in oil palm. The study used a quantitative method with a Completely Randomized Design (CRD), including Hatch and Carry distance treatments at radii of 10 m, 100 m, 200 m, 300 m, and 400 m, as well as assisted pollination techniques as a comparison. Data on fruit set and bunch weight were analyzed using analysis of variance (ANOVA) at the 95% confidence level, followed by the Duncan Multiple Range Test (DMRT). The results showed that the highest fruit set was observed at 10–200 m and was not significantly different, but decreased significantly at 300 m and 400 m. The same pattern also occurred for bunch weight, with the highest value at 100 m. The assisted pollination technique produces fruit set equivalent to the effective Hatch and Carry distance of 10–200 m. This study concluded that the effective distribution range of E. kamerunicus is within a radius of 200–300 m; thus, Hatch and Carry technology has the potential to be an efficient alternative for increasing oil palm productivity.